ANALISIS KEUNTUNGAN FINANSIAL USAHA PENGGEMUKAN SAPI POTONG DI KABUPATEN BOJONEGORO - Retna D Lestari; Lukman M Baga; Rita Nurmalina (Universitas Sebelas Maret, 2015)
Cattle farm agribusiness in Indonesia is still a sector that needs to be developed, given the increasing demand for meat, but has not met from domestic meat production. One of the efforts to achieve stability availability of beef that is through an increase in beef cattle fattening which have long-term prospects. This study aims to identify and analyze the financial benefits fattening beef cattle in Bojonegoro which is one of the central areas of the cow kind Peranakan Ongole (PO) in the province of East Java. Data were analyzed quantitatively by using indicators of profitability and feasibility ie B / C Ratio, Break Even Point, Net Present Value, Internal Rate of Return, and Payback Period. The research location in the village Napis, District Tambakrejo with 30 respondents breeders who do fattening for 4 months. The results showed the average value of B / C ratio of 1.23, NPV of USD 481 110, 59, IRR 11.30%, and PBP for 2 years and 9 months. Based on the research results can be suggested to the Government of Bojonegoro in order to provide guidance and directs farmers to conduct fattening cattle given the small number of farmers who cultivate the cow on a large scale.